2017
DOI: 10.1113/jp273915
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of cell‐level neurophysiological diversity in the rostral nucleus reuniens of adult mice

Abstract: The nucleus reuniens (Re) is the largest of the midline thalamic nuclei. We have performed a detailed neurophysiological characterization of neurons in the rostral Re of brain slices prepared from adult male mice. At resting potential (-63.7 ± 0.6 mV), ∼90% of Re neurons fired action potentials, typically continuously at ∼8 Hz. Although Re neurons experience a significant spontaneous barrage of fast, amino-acid-mediate synaptic transmission, this was not predominantly responsible for spontaneous spiking becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 66 publications
(174 reference statements)
2
29
0
Order By: Relevance
“…Interestingly, this did not correspond to a significant decrease in the number of neurons exhibiting 120 spontaneous AP generation in the absence of applied stimuli ( Fig 1B, (Walsh et al, 2017) and found, predictably, that Vm varies between these populations. As 124 such, the increased proportion of hyperpolarised neurons in J20 mice could be a manifestation of an 125 increase in the relative proportion of active neurons displaying low firing frequencies associated with 126 hyperpolarised Vm.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…Interestingly, this did not correspond to a significant decrease in the number of neurons exhibiting 120 spontaneous AP generation in the absence of applied stimuli ( Fig 1B, (Walsh et al, 2017) and found, predictably, that Vm varies between these populations. As 124 such, the increased proportion of hyperpolarised neurons in J20 mice could be a manifestation of an 125 increase in the relative proportion of active neurons displaying low firing frequencies associated with 126 hyperpolarised Vm.…”
mentioning
confidence: 85%
“…95% O2 82 /5% CO2). A single coronal section containing the rostral Re was identified as described previously 83 (Walsh et al, 2017). 84…”
Section: Animals and Tissue Preparation 72mentioning
confidence: 99%
See 3 more Smart Citations